2023
DOI: 10.1002/vjch.202200138
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and equilibrium studies on bioadsorption of copper and lead by water hyacinth (Eichhornia crassipes) plant powder

Linton Hazarika,
Kishor Kr. Shah,
Gitali Baruah
et al.

Abstract: Common water hyacinth plant (Eichhornia crassipes) found in various water bodies in Assam, India, was used as bioadsorbent for removal of toxic metals (Cu and Pb) from synthetic medium. The functional groups present in the bioadsorbent, water hyacinth plant powder (WPP) were determined by using Fourier transform infra red spectroscopy (FTIR) and surface topography by scanning electron microscopy (SEM) technique. The specific surface area of WPP was also determined. The optimum adsorption properties of WPP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Continuous treatment systems with fixed biomass have been used to purify water by exposing it to cellulose. This novel method yields reliable results and could be implemented in industries that contaminate water resources with their effluents [7][8][9][10]. Continuous systems are economical and easy to construct, as they are made with recycled materials [11].…”
Section: Introductionmentioning
confidence: 96%
“…Continuous treatment systems with fixed biomass have been used to purify water by exposing it to cellulose. This novel method yields reliable results and could be implemented in industries that contaminate water resources with their effluents [7][8][9][10]. Continuous systems are economical and easy to construct, as they are made with recycled materials [11].…”
Section: Introductionmentioning
confidence: 96%
“…Water hyacinth (Eichornia crassipes) has been used as a biosorbent for heavy metal removal [19][20][21][22][23][24][25]. Roots and stems are parts of water hyacinth widely used as a biosorbent [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Roots and stems are parts of water hyacinth widely used as a biosorbent [19][20][21][22]. Only a few studies reported the utilization of water hyacinth leaf as a biosorbent [23][24][25].…”
Section: Introductionmentioning
confidence: 99%